2007
DOI: 10.1177/1934578x0700200117
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of the Essential Oil of Lippia oreganoides against Multiresistant Bacterial Strains of Nosocomial Origin

Abstract: Antibacterial activity of the essential oil of Lippia oreganoides was evaluated against thirty-nine multiresistant bacterial strains of nosocomial origin and five reference bacterial strains using the disk diffusion agar method. The results obtained have revealed strong antibacterial activity against methicillin resistant Staphylococcus aureus, extended spectrum β-lactamase producing Klebsiella pneumoniae, and multiresistant Acinetobacter baumannii with MIC values ranging from 20 to 40 μg/mL. The low dose anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
12
0
4
Order By: Relevance
“…Both chemotypes are found in Brazil and Venezuela, countries neighboring Colombia. Their high antimicrobial activity 15, 27 could be attributed to their major compounds, carvacrol and thymol. However, to our knowledge, L. origanoides chemotype A has not been reported to this date in other countries.…”
Section: Resultsmentioning
confidence: 99%
“…Both chemotypes are found in Brazil and Venezuela, countries neighboring Colombia. Their high antimicrobial activity 15, 27 could be attributed to their major compounds, carvacrol and thymol. However, to our knowledge, L. origanoides chemotype A has not been reported to this date in other countries.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial method: The antimicrobial assay was carried out according to the disc diffusion method described by Rondón et al [11], as reported in our earlier publication [12].…”
Section: Methodsmentioning
confidence: 99%
“…Actividad antibacteriana.-La actividad antibacteriana fue evaluada de acuerdo al método de difusión en agar con discos descrita por Velasco et al (2007), los ensayos se realizaron por duplicado.…”
Section: Análisis De Composición Químicaunclassified